Efektivitas Media Video Tutorial dalam Keterampilan Vokasional Membuat Ikan Asin bagi Anak Tunarungu - Putri, Lisa Yulia (journal of residu, 2019)
This research is motivated by the problems found in the field there are five deaf children of class X in SLB YPPC Painan. When researchers observed children who were not interested in learning about fish processing, children had never been tried on how to process fish to be processed products that could be traded. This study aims to prove the effectiveness of video tutorial media in the vocational skills of making salted fish for class X deaf children in SLB YPPC Painan. he research method used in this method is the pre experimental design or quasi experimental method. This study consists of several stages, namely the initial stage to determine the child's value before being given a treatment (pretest), the second stage is giving treatment (treatment), and the third stage is after being given treatment (posttest). The results of the work process of five children in making salted fish after being processed and compared using the Wilcoxon sign rank test, proved that the video tutorial media was effectively used in vocational skills in making salted fish for deaf children in SLB YPPC Painan.